On the performance analysis of hybrid-duplex systems for aeronautical communications - Tan, Ernest Zheng Hui (2020)
Air traffic growth is expected to rise sharply in the near future, causing a swell in data communication demands on the congested aeronautical spectrum which cannot be met with existing aeronautical communication systems. To this end, a hybrid-duplex (HBD) aeronautical communications system consisting of a full-duplex (FD) enabled ground station, and legacy half-duplex (HD) air- stations is proposed as a direct solution to boost spectral efficiency. In particular, the system level outage probabilities and transmission power requirements of the proposed HBD and HD aeronautical communication systems are analyzed. Performance analysis shows that the proposed HBD system can attain better outage performance in the en route scenario. The proposed HBD system is also able to support an equivalent data rate as an HD system with lower transmit power and signal-to- interference-plus-noise-ratio (SINR) requirements and longer transmission range when inter-aircraft interference and residual self-interference is kept sufficiently low.